2014
DOI: 10.1007/s10096-014-2211-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a commercial real-time PCR assay for Aspergillus DNA detection in serum samples from high-risk patients: comparison with a galactomannan enzyme immunoassay

Abstract: We investigated the clinical performance of a polymerase chain reaction (PCR)-based commercial platform, the Myconostica MycAssay™ Aspergillus (MAP), for fungal DNA detection in the serum of patients at risk of invasive aspergillosis (IA). Sixty-four hospitalized patients were prospectively enrolled and a total of 71 different episodes were investigated (30 episodes were clinically/microbiologically classified as IA and 41 as control episodes). When MAP was compared to the galactomannan (GM) assay, no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, it remains unclear whether SeptiFast ® will be available in the future. Similarly, the PCR platform Myconostica MycAssay ™ Aspergillus (MAP) was found to be equally sensitive and specific as compared to Aspergillus GM in high‐risk haematological patients …”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…However, it remains unclear whether SeptiFast ® will be available in the future. Similarly, the PCR platform Myconostica MycAssay ™ Aspergillus (MAP) was found to be equally sensitive and specific as compared to Aspergillus GM in high‐risk haematological patients …”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…They concluded that the combination of different biomarkers and test, combined with CT scan results, could be beneficial to improve diagnostic specificity, sensitivity and, in particular, negative predictive values. Other authors have recommended similar strategies, combining results from the lateral-flow device (LFD) test and PCR [56], LFD and GM tests [48], and PCR and GM test [44,45,57]. These studies included only few SOT patients, but the results suggest that the combined use of several biomarkers and clinical parameters could provide a better diagnostic power also in SOT patients with suspected IMI.…”
Section: Epidemiology and Diagnosis Of Imimentioning
confidence: 99%
“…More recently, a PCR commercial assay (MycAssay™ Aspergillus, Myconostica) became available for the diagnosis of fungal DNA in the serum and bronchoalveolar lavage fluids of patients at risk of IA. Overall, PCR-based assays have advantages over the galactomannan assay, namely detection at the species level, where timing is critical (hours vs. days), provides higher specificity and (or) sensitivity, and when low fungal levels are present (Guinea et al 2013;Orsi et al 2015;Pini et al 2015;Torelli et al 2011). Unfortunately, it requires more expensive equipment, false positives and negatives through cross-reactivity can be generated, it involves rigorous standardization and validation methods, and PCR inhibitors can interfere with the results (Steinbach 2013;Morton et al 2017).…”
Section: Diagnosismentioning
confidence: 99%